Crop rotations reduce pathogenic fungi compared to continuous cropping - Yanhui Dou; Shuting Yu; Song Liu; Tingting Cui; Rongyan Huang; Yushu Wang; Junqiang Wang; Kefei Tan; Xinyuan Li (Rhizosphere, 2025)

Spatial-Temporal Ship Pollution Distribution Exploitation and Harbor Environmental Impact Analysis via Large-Scale AIS Data - Xinqiang Chen; Shuting Dou; Tianqi Song; Huafeng Wu; Yang Sun; Jiangfeng Xian (Journal of Marine Science and Engineering, 2024)
Ship pollution emissions have attracted increasing attention in the maritime field due to the massive growth of maritime traffic activities. It is important to identify the ship emissions (SEs) magnitude and corresponding spatial and temporal distributions for the purposes of developing appropriate strategies to mitigate environment pollution. The aim of this study was to estimate ship pollution emissions with various typical merchant ship types under different sailing conditions. We estimated the emission variation with a ship traffic emission assessment model (STEAM2), and then the ship pollution emission distribution was further visualized using ArcGIS. We collected data from the automatic identification system (AIS) for ships in New York Harbor and further analyzed the spatiotemporal distribution of pollutant emissions from ships. The experimental results demonstrate that the ship pollutant emission volume in the New York Harbor area in 2022 was 3340 t, while the pollution in terms of CO, SO2, CXHX, PM10, NOX, and PM2.5 was 136, 1421, 66, 185, 1384, and 148 t, respectively. The overall SEs from container ships, passenger ships, and tankers account for a large amount of pollution discharge. The pollutant emissions of container ships are significantly greater than that of their counterparts. Moreover, the spatiotemporal distributions of ship pollutant discharge can vary significantly among different ship types and sailing conditions.

Mettl13 protects against cardiac contractile dysfunction by negatively regulating C-Cbl-mediated ubiquitination of SERCA2a in ischemic heart failure - Shuting Yu; ZhiYong Sun; Xiuzhu Wang; Tiantian Ju; Changhao Wang; Yingqi Liu; Zhezhe Qu; KuiWu Liu; Zhongting Mei; Na Li; Meixi Lu; Fan Wu; et al. (Science China Life Sciences, 2023)

N-methylpiperazine-diepoxyovatodiolide ameliorates peritoneal fibrosis via suppressing TGF-β/Smad and JAK/STAT signaling pathway - Min Mo; Yao Zeng; Yiqun Zeng; Shuting Li; Xiaoyang He; Xiaowen Chen; Qimei Luo; Mi Liu; Congwei Luo; Xianrui Dou; Fenfen Peng; Haibo Long (Chemico-Biological Interactions, 2023)